2022
DOI: 10.3390/genes13020329
|View full text |Cite
|
Sign up to set email alerts
|

The Caucasian Clover Gene TaMYC2 Responds to Abiotic Stress and Improves Tolerance by Increasing the Activity of Antioxidant Enzymes

Abstract: Abiotic stress affects metabolic processes in plants and restricts plant growth and development. In this experiment, Caucasian clover (Trifolium ambiguum M. Bieb.) was used as a material, and the CDS of TaMYC2, which is involved in regulating the response to abiotic stress, was cloned. The CDS of TaMYC2 was 726 bp in length and encoded 241 amino acids. The protein encoded by TaMYC2 was determined to be unstable, be highly hydrophilic, and contain 23 phosphorylation sites. Subcellular localization results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Bieb.) by increasing antioxidant enzymes’ activities ( Zhao et al., 2022 ). It has also found that TaMYC2 overexpression significantly improved drought and cold tolerance of transgenic tobacco by increasing these activities.…”
Section: Discussionmentioning
confidence: 99%
“…Bieb.) by increasing antioxidant enzymes’ activities ( Zhao et al., 2022 ). It has also found that TaMYC2 overexpression significantly improved drought and cold tolerance of transgenic tobacco by increasing these activities.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that TaeRF1 plays an active regulatory role in the responses of plants to LT stress. At the same time, TaMYC2 in Caucasian clover can also increase the activity of antioxidant enzymes in plants, and increase the expression of ROS scavenging related genes and stress response genes under LT and drought stress, thereby enhancing the response ability of transgenic plants to stress ( Zhao et al., 2022 ). Taken together, these findings provide further insights into the properties of TaeRF1 protein and how it protects plants at low temperatures, and provide references for clover breeding.…”
Section: Discussionmentioning
confidence: 99%